THE EFFECT OF SEFT THERAPY ON THE LEVEL OF DYSMENORAL PAIN IN UMP STUDENTS - Hardiyani, Tati; Utami, Hernastiti Sedya; Grafiyana, Gisella Arnis (Universitas Negeri Gorontalo, 2025)
Dysmenorrhoea is a painful disorder that most women experience every month. The impact that occurs if dysmenorrhea is left untreated or not treated properly is that it can cause disruption of daily activities, infertility, undetected pregnancy, ectopic cyst rupture, uterine perforation from the IUD and infection. Based on these impacts, dysmenorrhea must be treated immediately, so that these impacts do not interfere with daily activities or activities as well as a person's psychological condition. One non-pharmacological technique to reduce dysmenorrhea is SEFT therapy. Spiritual Emotional Freedom Technique (SEFT) is a complementary therapy in the Mind-Body Therapy category, which can be used to treat physical problems including dysmenorrhea pain. Based on the description above, researchers are interested in researching